Arabic Sign Language Recognition in Real Time Using Transfer Deep Learning - Noura Alshareef; Rema Abobake; Asma Abd Aljalil (AlQalam Journal of Medical and Applied Sciences, 2024)
People with hearing and speech disabilities in Arab society have obstacles to communicate since Arabic sign language (ArSL) has not been widely understood among society’s members. Using technology to translate hand gestures from (ArSL) to written Arabic language can help bridge communication gaps and break down disability barriers in Arab society. latest research utilizes the camera to record the user’s hand features to recognize its gestures. In this research a software was developed to recognize ArSL hand gestures in real time and immediately translate them to written alphabet Arabic letters utilizing Convolutional Neural Networks (CNNs), Teachable Machine. Our methodology involves data collection and preparation, Therefore an ArSL alphabet database has been created, with 28 categories representing the Arabic letters. For each letter, 400 images were captured. Then 87.5% of the dataset was passed to Google’s Teachable Machine for training process, after that the dataset was tested and evaluated. Finally, the remaining 12.5% of dataset were used on local host for testing the model generated. The accuracy value for the model on local host was 92%. The experimental output shows the proposed model has good performance results in real time where the average recognition accuracy was 93.8%. في المجتمع العربي، يواجه الصم والبكم صعوبات في التواصل، إذ لم تنتشر لغة الإشارة العربية على نطاق واسع بين أفراد المجتمع. ولحل هذه المشكلة يمكن استخدام التقنيات الحديثة لترجمة إشارات اليد من لغة الإشارة العربية إلى اللغة العربية المكتوبة، مما سيساعد على سد هذه الفجوة وكسر الحواجز التي تعيق التواصل بينهم وبين باقي افراد المجتمع العربي. وتستخدم الأبحاث الحديثة الكاميرات لتسجيل ملامح يد المستخدم والتعرف على إشاراته وترجمتها الى لغة مكتوبة. في هذا البحث، تم تطوير برنامج لتحديد إشارات لغة الإشارة العربية في الوقت الفعلي وترجمتها فوراً إلى الأحرف العربية المكتوبة، باستخدام تقنيات الشبكات العصبية التلافيفية والنماذج القابلة للتعلم كـ"Teachable Machine" من جوجل. وتضمنت منهجية البحث جمع البيانات وإعدادها، حيث تم إنشاء قاعدة بيانات لأبجدية لغة الإشارة العربية، بـ28 فئة تمثل الحروف العربية. وتم التقاط 400 صورة لكل حرف. ثم تم استخدام 87.5% من البيانات لتدريب نموذج "Teachable Machine"، بينما استخدم 12.5% المتبقية لاختبار النموذج المطور محلياً. وقد بلغت دقة النموذج 92% في الاختبارات المحلية، كما كانت دقة التعرف على الإشارات في الوقت الاني 93.8% في المتوسط.